Research on common medical data model and establishment of cross-cohort models at home and abroad - Jiaqi CHEN; Ming LÜ; Ze WANG; Xiaorong YANG; Ruijie WU; Tongchao ZHANG; Zilin LI; Yuan ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
The phenomenon of "information islands" in medical studies is becoming increasingly prevalent since healthcare information resources are generally characterized by multiple sources, multiple types, and non-standardization. The data from large cohort studies in China have complex sources and multiple types and it is difficult for the data from different cohorts to be integrated, shared and utilized. For promoting the standardized integration of healthcare resource data in China, we conduct an in-depth literature analysis on the research on common medical data models (CDM) at home and abroad and patterns of CDM establishment for cross-cohort studies. The study also proposes some recommendations regarding the problems of medical data integration and sharing in the context of precision medicine in China for effective integration, consolidation, sharing, and utilization of cross-cohorts data.